The Oxford encyclopedia of Buddhism - Payne, Richard K.; Halkias, Georgios T. (Oxford University Press, 2024)
"The earliest examples of Buddhist studies originating in the Western world tended to frame the religion in ways similar to Christianity or Judaism. This involved, among other things, an emphasis on doctrine, and an assumption that the Buddha is directly comparable to the Christ figure. Starting in the late twentieth century, Buddhist studies scholars have been creatively moving outside of this rubric. This wider approach fosters a greater awareness of external versus internal critiques of the religion, an inclusion of new disciplines and previously marginalized voices, and an appreciation of the varied personal experiences of lived practice. As a result, Buddhist studies has attracted a growing audience within the humanities and has been at the forefront of the discourse on cultural exchange and the changing religious landscape. Reflecting these innovations, The Oxford Encyclopedia of Buddhism is a first of its kind reference project: a systematic effort to analyze the ways in which Buddhist studies has developed as well as the new sub-fields of inquiry. Consisting of 134 chapters, the Encyclopedia covers several major thematic areas, including historical and historiographical studies, art and architecture, social and academic issues, philosophical and doctrinal studies, textual and philological studies, and the most influential educational institutions. The Encyclopedia frames Buddhist studies as a field rather than a discipline, which means that it is intended to cover a rich variety of intellectual projects that allow for both independent and interconnected areas of study. It is this perspective, gazing toward the future of the field, that marks the volume as an essential work of scholarship and an evolving encyclopedia for study and research"--